2018
DOI: 10.1021/acssuschemeng.7b04070
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Antioxidant Performance of Lignin by Enzymatic Treatment with Laccase

Abstract: The utilization of lignin is of high interest since it represents the most abundant polyphenol worldwide. For the application of lignin as a natural antioxidant more phenolic hydroxyl groups (Ph−OH) and lower molecular weight (M w ) are essential. Here, we proposed a green method based on enzymatic treatment of two lignins (alkaline lignin AL and hydrolysis lignin HL) with laccase, by which the structure, especially the Ph−OH contents and M w of lignin, could effectively controlled. The antioxidant activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
42
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(51 citation statements)
references
References 30 publications
(43 reference statements)
5
42
0
1
Order By: Relevance
“…Many researchers are currently investigating these properties. For example, Li et al (2018) proposed improving the antioxidant properties of two lignins by enzymatic treatment with laccase. The obtained results showed that the enzymatically treated lignin with the highest Ph-OH content and lower M w value possessed the strongest antioxidant activity, which is higher than that of commercial antioxidants.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers are currently investigating these properties. For example, Li et al (2018) proposed improving the antioxidant properties of two lignins by enzymatic treatment with laccase. The obtained results showed that the enzymatically treated lignin with the highest Ph-OH content and lower M w value possessed the strongest antioxidant activity, which is higher than that of commercial antioxidants.…”
Section: Introductionmentioning
confidence: 99%
“…Both processes, lignin removal and modification, now aim at the production of either small compounds as novel chemical building blocks, or at the development of new biomass-based materials. Recent examples include the production of benzaldehyde compounds and vanillin from lignin [78], the development of lignin-based controlled-release fertilizers [79], and the improvement of antioxidant activity of lignin [80], but also the modification of pulp for wood fiber insulation boards manufacturing [81]. Indeed, recent patents regarding the use of laccases in the paper industry are mostly dedicated to the incremental improvements of the established processes either through the addition of chemical mediators or the improved laccase variants (CN108823177A, CN109098025A).…”
Section: Lignin Removal and Modificationmentioning
confidence: 99%
“…Abundant research has focused on lignin treat as heavy metal adsorbent, since it is abundance in nature, environmental friendly, thermal stability, and easy to access [108][109][110][111]. However, the research progress of ligninbased adsorbents is slow and the adsorption capacity is very low, for example, the heavy metals removal by lignin grafted polyacrylic acid is only 70.1 mg/g, 7.7 mg/g, and 5.3 mg/g for Cd 2+ , Co 2+ , and Hg 2+ , respectively [112,113].…”
Section: Lignin Modificationmentioning
confidence: 99%